UPAYA GURU DALAM MENINGKATKAN MINAT MEMBACA SISWA DI SDN AGOWOE MELALUI KEGIATAN LITERASI - Anastasia Moi Nilu; Maria Katarina Mau Keno; Fransiska Maria Mulu Keti; Anastasia Azi; Ermelinda Yosefa Awe (STKIP Subang, 2025)
This study aims to describe teachers' efforts to increase students' interest in reading at SDN Agowoe through literacy activities. Low student interest in reading is a challenge that impacts the learning process, so teachers' active role is needed in creating interesting and sustainable literacy strategies. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The subjects in this study, class teachers, and students at SDN Agowoe. The results show that teachers and students carry out various literacy activities such as a 15-minute reading program before learning and the provision of reading corners in the classroom. In addition, the use of library facilities also supports the creation of a literacy culture in the school. These efforts have succeeded in increasing students' interest in reading, as seen from their enthusiasm and participation in various reading activities. The role of teachers as literacy facilitators is very important in forming reading habits from an early age in the elementary school environment.